男性气概的协商 ：《弁而钗》同性情欲的一种观察 = Negotiating masculinities : an observation of homosexuality in bian er chai - 李梅银 Li, Meiyin (Nanyang Technological University, 2021)
古代中国的同性恋现象作为一种亚文化具有研究意义。《弁而钗》受晚明崇情思想影响，被认为是真正正面描写同性恋的小说集。本文以男性气概的性别概念分析当中同性恋的主/从关系和情欲表现，探讨同性恋如何借由协商双方的男性气概而建构、发展和消解。第一章将梳理中国同性恋传统与晚明的崇情思想，为分析《弁而钗》文本做相关社会背景和文化思想的介绍；第二章着手《弁而钗》的文本细读，阐述男性气概的协商原因和表现，及同性恋的社会处境；第三章推测《弁而钗》男性气概的协商的文化心理。The phenomenon of homosexuality in ancient China is of great significance as a subculture research topic. Being influenced by the thought of honoring qing in late Ming, Bian er chai is considered to be a collection of novels that truly describe homosexuality. This thesis uses the concept of masculinity to analyse the dominant/submissive relationship and erotic performance of homosexuals and explore how the negotiation of masculinities has enabled homosexuality to be constructed, developed and de-constructed. The first chapter will summarise the history of homosexual tradition in ancient China and introduce the thought of honoring qing in late Ming, this is to set the context of the thesis. The second chapter will analyse the text of Bian er chai and discuss the reasons and performance of negotiating masculinities, as well as to examine the social situation of homosexuality in ancient China. The third chapter will discuss the cultural psychology behind this observation.